2016
DOI: 10.1177/0145721716658976
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of the Quality and Outcomes of Diabetes Education Programs for Children and Adolescents

Abstract: Various avenues can be considered to improve participant engagement in education programs and to align these programs more closely with international recommendations. Further research is required to enhance knowledge in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
0
15
0
3
Order By: Relevance
“…The quality of the educational interventions was assessed using the International Society for Pediatric and Adolescent Diabetes (ISPAD) recommendations, according to the 19 key criteria selected by Colson et al These recommendations evaluate the impact of educational interventions on both diabetes knowledge and psychosocial outcomes such as self‐management, and belong to the ISPAD Guidelines from 2009 and 2014, subsequently updated with the new recommendations published in 2018 . The 19 key criteria were organized into three categories: (a) general recommendations, containing seven criteria, (b) universal principles, containing five criteria and (c) characteristics of a structured education programme, containing seven criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the educational interventions was assessed using the International Society for Pediatric and Adolescent Diabetes (ISPAD) recommendations, according to the 19 key criteria selected by Colson et al These recommendations evaluate the impact of educational interventions on both diabetes knowledge and psychosocial outcomes such as self‐management, and belong to the ISPAD Guidelines from 2009 and 2014, subsequently updated with the new recommendations published in 2018 . The 19 key criteria were organized into three categories: (a) general recommendations, containing seven criteria, (b) universal principles, containing five criteria and (c) characteristics of a structured education programme, containing seven criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Every intervention was assigned a global score out of 19 based on the number of recommendations met, followed by a second score by category identifying the weak points (Table 4). A second score <50% indicates the need to improve the educational programme in that category in relation to the ISPAD guidelines . The quality assessment was conducted by one coder and checked by three other coders.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2001 review evaluating the effectiveness of psychoeducational interventions in adolescents with T1DM, Hampson et al observed that most interventions were associated with a small (0.6%) and a non‐significant reduction in HbA1c levels . In recent years, several systematic reviews have been conducted to evaluate the metabolic impact of education programs on patients with T1DM . One of the reviews pointed out to a lack of well‐delineated studies and a great heterogeneity among the methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies, this one also showed metabolic improvement with the intervention at 12 months (0.11, 95% CI −0.28 to 0.50, P = .584) and 24 months (0.03, 95% CI −0.36 to 0.41, P = .891) of follow‐up. Colson et al revised 2528 studies assessing educational interventions for diabetes and identified 43 programs targeting youths with T1DM. The programs varied widely in terms of organization, procedure, and content.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the international debate concerning educational programs in diabetes education, many other interventions have been developed and evaluated. However, few programs seem to address psychosocial indicators [48].…”
Section: Discussionmentioning
confidence: 99%